A Novel Mn(II) Complex: Synthesis, Characterization and Magnetic Property - Hu, Jing; Ping Wang, Li (Asian Journal of Chemistry, 2013)
A new Mn(II) complex: [Mn(HBTC)(H2O)3] where HBTC = 1,3,5-benzene tricarboxylic acid has been synthesized and characterized by IR spectra and elemental analysis. The relationship between the temperature and the magnetic susceptibility of the complex over the range 5 300 K indicates the presence of a antiferromagnetic interactions in the Mn(II) ions of the complex.